Hydrological Risk - World Bank (World Bank, Washington, DC, 2021)
This Technical Note contains a level of technical detail that non-specialists can use for guidance in addressing the hydrological aspects of dam projects early in the project preparation. It is intended to raise awareness and inform specific studies and investigations, as appropriate, during project preparation and implementation. The material presented should be used to prepare terms of reference on such studies and to assess the adequacy of methodology proposed by consultants in response to tenders for advisory services. It is recommended that, reading the Note, the client and the World Bank project teams will assess the required level of hydrological expertise in the teams. The hydrological subjects this Note covers are typical in World Bank–supported operations. There are several other subjects pertaining to hydrology that it does not cover. Enlarging the scope to those subjects will defeat the objective and turn the Note into a handbook on the vast discipline of hydrology. The same selective effort has been applied in choosing the references that the reader can consult to focus on specific subjects. For that reason, the list has been limited to essential references that provide general guidance on required hydrology studies, whereas the additional sources complement the general guidance with references dealing with specific aspects of the project hydrology.